Male Reproductive Anatomy 2022
DOI: 10.5772/intechopen.98798
|View full text |Cite
|
Sign up to set email alerts
|

Positional Relationships among Male Reproductive Organs in Insects

Abstract: The location, morphology and function of male internal reproductive organs in insects have been extensively studied, but the relative positioning of those organs is less understood. Position and morphology of the testis, vas deferens, seminal vesicle, accessory gland and ejaculatory duct determine the migration or ejaculation of sperm and other substances. In species where the testis is connected with the seminal vesicle directly or the seminal vesicle is lacking, males usually store complete sperm in the test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…In lepidopteran insects, sperms are not mature in the testis and change morphologically when passing through the vas efferens from the testis to the vas deferens. Hiroyoshi and Reddy (2021) discussed positional relationships of male reproductive organs and how this relates to their morphology and function with a focus on sperm maturation and transfer. However, Omura (1938b) reported that though spermatozoa attain full maturity in the testis in B. mori they remain inactive throughout the post testicular organs and become vigorously active only when get mixed with The female reproductive system consists of a pair of ovary, each with four ovarioles, paired lateral oviducts which joins to form a common oviduct which has a dorsal protrusion, the vestibulum, a bursa copulatrix, a spermatheca and a pair of female accessory glands or dorsal colleterial glands with their reservoirs (Fig.…”
Section: Morphologymentioning
confidence: 99%
“…In lepidopteran insects, sperms are not mature in the testis and change morphologically when passing through the vas efferens from the testis to the vas deferens. Hiroyoshi and Reddy (2021) discussed positional relationships of male reproductive organs and how this relates to their morphology and function with a focus on sperm maturation and transfer. However, Omura (1938b) reported that though spermatozoa attain full maturity in the testis in B. mori they remain inactive throughout the post testicular organs and become vigorously active only when get mixed with The female reproductive system consists of a pair of ovary, each with four ovarioles, paired lateral oviducts which joins to form a common oviduct which has a dorsal protrusion, the vestibulum, a bursa copulatrix, a spermatheca and a pair of female accessory glands or dorsal colleterial glands with their reservoirs (Fig.…”
Section: Morphologymentioning
confidence: 99%